2011
DOI: 10.1097/pcc.0b013e3181d8e348
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury and renal replacement therapy independently predict mortality in neonatal and pediatric noncardiac patients on extracorporeal membrane oxygenation

Abstract: After adjusting for known predictors of mortality, AKI and RRT independently predict mortality in neonates and children, who receive extracorporeal membrane oxygenation. Ascertainment of AKI risk factors, testing novel therapies, and optimizing the timing/delivery of RRT may positively impact survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(135 citation statements)
references
References 12 publications
9
122
2
2
Order By: Relevance
“…The following variables were chosen: calendar year in which ECMO was delivered (15,23); patient age (23)(24)(25); primary diagnosis (23)(24)(25)(26)(27); ECMO support type (16,27); presence of pre-ECMO acute renal failure (23,26,27); presence of comorbid conditions (23,28); pre-ECMO cardiac arrest (25,29); and pre-ECMO measures including duration of mechanical ventilation (23,25,30), arterial blood pH (23,27,31), Pa CO 2 (25), and the ratio of arterial partial pressure of oxygen to fraction of inspired oxygen (PF ratio) (1,23). In neonatal patients, case-mix was also adjusted for gestational age (24) and birth weight (24).…”
Section: Selection Of Variables and Risk Adjustmentmentioning
confidence: 99%
“…The following variables were chosen: calendar year in which ECMO was delivered (15,23); patient age (23)(24)(25); primary diagnosis (23)(24)(25)(26)(27); ECMO support type (16,27); presence of pre-ECMO acute renal failure (23,26,27); presence of comorbid conditions (23,28); pre-ECMO cardiac arrest (25,29); and pre-ECMO measures including duration of mechanical ventilation (23,25,30), arterial blood pH (23,27,31), Pa CO 2 (25), and the ratio of arterial partial pressure of oxygen to fraction of inspired oxygen (PF ratio) (1,23). In neonatal patients, case-mix was also adjusted for gestational age (24) and birth weight (24).…”
Section: Selection Of Variables and Risk Adjustmentmentioning
confidence: 99%
“…As in critically ill patients who have not used ECMO supportive therapy, AKI and fluid overload are also associated with worse outcomes for patients on ECMO [9,10]. Despite the importance of managing these conditions in these individuals, the procedural recommendations are based solely on isolated data from centers that have experience in managing these patients.…”
Section: Acute Kidney Injury and Ecmomentioning
confidence: 99%
“…Moreover, AKI is an independent risk factor for prolonged mechanical ventilation and pediatric ICU mortality (1,4). Recently, our group and other research groups reported high incidences of AKI in children treated with extracorporeal membrane oxygenation (ECMO), who tend to be the most critically ill admitted to an ICU (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%